Jual Beli Durian Busuk Di Tinjau Dari Fiqh Muamalah - Borkat Halomoan Siregar & Fatahuddin Aziz Siregar & Ahmatnijar (Jurnal El-Thawalib, 2020)
In daily life, humans are required to always practice Allah's practice as an aspect of spiritual life, as well as to always practice habl min an-nas as an aspect of material life. Human life is never separated from the muamalah field as a social relationship between humans in meeting all their daily needs.Based on the above background, the purpose of this study is to know how the practice of buying and selling rotten durian and how the practice of buying and selling rotten durian is reviewed from fiqh muamalah. Based on the above background, the purpose of this study is to know how the practice of buying and selling rotten durian and how the practice of buying and selling rotten durian is reviewed from fiqh muamalah.This research is a field research using primary data and secondary data, and data collection in this study uses the observation method, interview method and documentation method.Based on the results of the above research, it is found that the practice of buying and selling rotten durians at the time of the sale and purchase agreement in Silaiya Village, Sayur Matinggi District, South Tapanuli Regency, the seller informed the buyer that the fruit he was selling was damaged fruit. However, in the practice of buying and selling rotten durians, the durian being traded has no measure or scale only by estimating the price, this kind of buying and selling is not allowed in Islam because every object being traded must have clear prices, quality and scales. or measure.